"I'm a Teacher, Unofficially": How Home-Based Providers Perceive and Navigate Their Roles. Issue 2 (2nd April 2020) - Hooper, Alison
ABSTRACT: Home-based child care is a widely used form of child care. However, little is known about the heterogeneous group of caregivers that make up the home-based provider workforce and how they view themselves and their work. This study used role theory as a framework for understanding how providers view and navigate their roles. Qualitative interviews were conducted with 29 home-based child care providers. Participants identified the roles that made up their role set, how they manage multiple roles, and the challenges they face in balancing these roles. Results suggest that participants can easily identify their multiple roles. The roles participants named aligned into three broad categories: functional, relational, and professional. Participants identified a number of strategies they use to manage roles, including finding an assistant or preparing outside child care hours, but results suggest they may benefit from more assistance in managing their multiple roles.